In vivo peripheral nerve activation using sinusoidal low‐frequency alternating currents. Issue 10 (30th June 2022) - Alhawwash, Awadh; Muzquiz, M. Ivette; Richardson, Lindsay; Vetter, Christian; Smolik, Macallister; Goodwill, Adam; Yoshida, Ken
Abstract: Background: The sinusoidal low‐frequency alternating current (LFAC) waveform was explored recently as a novel means to evoke nerve conduction block. In the present work, we explored whether increasing the amplitude of the LFAC waveform results in nerve fiber activation in autonomic nerves. In‐silico methods and preliminary work in somatic nerves indicated a potential frequency dependency on the threshold of activation. The Hering‐Breuer (HB) reflex was used as a biomarker to detect cervical vagus nerve activation. Methods: Experiments were conducted in isoflurane‐anesthetized swine ( n = 5). Two stimulating bipolar cuff electrodes and a tripolar recording cuff electrode were implanted on the left vagus nerve. To ensure the electrical stimulation affects only the afferent pathways, the nerve was crushed caudal to the electrodes to eliminate cardiac effects. (1) Standard pulse stimulation (Vstim) using a monophasic train of pulses was applied through the caudal electrode to elicit HB reflex and to identify the activated nerve fiber type. (2) Continuous sinusoidal LFAC waveform with a frequency ranging from 5 through 20 Hz was applied to the rostral electrode without Vstim to explore the activation thresholds at each LFAC frequency. In both cases, the activation of nerve fibers was detected by a HB reflex‐induced reduction in the breathing rate. Results: LFAC was found to be capable of eliciting an HB response. The LFAC activation thresholds were found to be frequency‐dependent. The HB threshold was 1.02 ± 0.3 mAp at 5 Hz, 0.66 ± 0.3 mAp at 10 Hz, and 0.44 ± 0.2 mAp at 20 Hz. In comparison, it was 0.7 ± 0.47 mA for a 100 μs pulse. The LFAC amplitude was within the linear limits of the electrode interface. Damage to the cuff electrodes or the nerve tissues was not observed. Analysis of Vstim‐based compound nerve action potentials (CNAP) indicated that the decrease in breathing rate was found to be correlated with the activation of slower components of the CNAP suggesting that LFAC reached and elicited responses from these slower fibers associated with afferents projecting to the HB response. Conclusions: These results suggest the feasibility of the LFAC waveform at 5, 10, and 20 Hz to activate autonomic nerve fibers and potentially provide a new modality to the neurorehabilitation field. Abstract : This work explored the ability of a novel sinusoidal low‐frequency alternating current (LFAC) waveform to excite the cervical vagus nerve fibers in the anesthetized swine model. LFAC stimulation presented at 5, 10, and 20 Hz through bipolar cuff electrodes was able to elicit the Hering‐Breuer reflex indicating afferent nerve fiber activation in autonomic peripheral nerves. The peak current threshold for LFAC activation was frequency‐dependent with thresholds decreasing with increasing LFAC frequency.